Active individuals have high mitochondrial content and oxidative markers in their abdominal subcutaneous adipose tissue. Issue 12 (2nd November 2016) - Pino, Maria F.; Parsons, Stephanie A.; Smith, Steven R.; Sparks, Lauren M.
Abstract : Objective: Exercise training (training) effects on white adipose tissue (WAT) thermogenic and oxidative capacities in humans are inconclusive. This study aimed to investigate whether an active lifestyle is characterized by thermogenic and/or oxidative transcriptional markers in human WAT. Methods: In vivo maximal muscle ATP synthetic rates (ATPmax) were measured by 31 P‐MRS, body composition by DXA, and peak oxygen uptake (VO2 peak) by cycle ergometry in active ( n = 7) and sedentary (SED) individuals before and after 3 weeks of training ( n = 9, SED only). mRNA expressions of brown adipose and β‐oxidation markers, as well as mitochondrial DNA content (mtDNA), were measured by qRT‐PCR and qPCR, respectively, in WAT. Results: ATPmax and VO2 peak were higher in active versus SED individuals. Following training in SED individuals, ATPmax and VO2 peak increased. Proliferator‐activated receptor gamma coactivator‐1α and carnitine palmitoyltransferase‐1β gene expressions and mtDNA content were significantly higher in WAT of active versus SED individuals before training. mRNA contents of brown and beige‐specific markers were not different between cohorts. Training effectively increased ATPmax and VO2 peak but had no effect on mtDNA content or expressions of genes that regulate thermogenic and oxidative capacities in WAT. Conclusions: Results indicate that an active lifestyle is characterized by elevated mitochondrial content and oxidative, not thermogenic, markers of WAT.